ASME 2007 Internal Combustion Engine Division Fall Technical Conference 2007
DOI: 10.1115/icef2007-1630
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Combustion Control to Improve Diesel HCCI Cycle Fuel Efficiency

Abstract: Previous work indicates that the lowered combustion temperature in diesel engines is capable of reducing nitrogen oxides and soot simultaneously, which can be implemented by the heavy use of exhaust gas recirculation or the homogeneous charge compression ignition (HCCI) type of combustion. However, the fuel efficiency of the low temperature combustion cycles is commonly compromised with high levels of hydrocarbon and carbon monoxide emissions. Additionally, in cases of diesel HCCI cycles, the combustion proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This suggested that the mixing between the diesel and the premixed ethanol was still not complete; otherwise the combustion phasing should be insignificantly affected by the diesel SOI timing if HCCI combustion had been realized at the time. 25 With excessively advanced diesel SOI timing, and enhanced mixing, dual-fuel combustion changed to quasi-HCCI combustion, as is therefore indicated by the shortened CD.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the mixing between the diesel and the premixed ethanol was still not complete; otherwise the combustion phasing should be insignificantly affected by the diesel SOI timing if HCCI combustion had been realized at the time. 25 With excessively advanced diesel SOI timing, and enhanced mixing, dual-fuel combustion changed to quasi-HCCI combustion, as is therefore indicated by the shortened CD.…”
Section: Resultsmentioning
confidence: 99%
“…Ultra-low NOx was reached at about 14% intake oxygen concentrations, while the soot emissions remained less than 0.01 g/kWh 18 19 16 18…”
Section: Diesel-ethanol Ltcmentioning
confidence: 98%
“…For homogeneous charge compression ignition (HCCI) combustion enabled by early multiple injections, the start of combustion is mainly determined by the in-cylinder compression temperature and the chemical reactivity of the fuel and air mixture [14]. The fuel injection timing has a minor effect on the combustion phasing [15][16][17][18], while the higher engine load is another challenge for HCCI type of combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion phasing control of early-multi-injection HCCI is a challenge for extending engine load levels [10,11]. On the other hand, the engine operation region of LTC achieved by single-shot injection along with the heavy use of EGR is constrained into narrow corridors or isolated islands of intake boost, EGR ratio, and engine loads [12,13].…”
Section: Introductionmentioning
confidence: 99%